(untitled) (Academia Journal of Medicine, 2026)
Background: Artificial intelligence (AI) has rapidly emerged as a transformative technology in healthcare, including dentistry. AI-driven systems are increasingly being used for diagnostic imaging, treatment planning, and predictive analysis. Numerous systematic reviews have evaluated the role of AI across various dental specialties. However, a comprehensive synthesis of these reviews is lacking.Objective: This umbrella review aims to summarize and critically analyze the evidence from systematic reviews evaluating the applications and outcomes of artificial intelligence in dentistry.Methods: Electronic databases including PubMed, Scopus, and Google Scholar were searched for systematic reviews assessing artificial intelligence applications in dentistry. Reviews published in English that evaluated clinical, diagnostic, or educational applications of AI were included. Data extraction included author details, year of publication, focus area, and key findings. Results: A total of eight systematic reviews were included. The evidence suggests that AI is widely applied in dental radiology, orthodontics, pediatric dentistry, and implantology. AI-based systems demonstrated improved diagnostic accuracy in detecting dental caries, periodontal bone loss, and periapical lesions. Additionally, AI has shown promising potential in treatment planning and clinical decision support. However, limitations such as data heterogeneity, limited clinical validation, and ethical concerns were reported.Conclusion: Artificial intelligence demonstrates considerable potential to enhance diagnostic accuracy and clinical efficiency in dentistry. Despite encouraging findings, further high-quality clinical studies and standardized validation protocols are required before widespread integration of AI technologies in routine dental practice.